Perbandingan Peta Kognitif Mahasiswa Baru Arsitektur dan Bukan Arsitektur pada Landmark Kampus Institut Teknologi Bandung - Widya, Amelia Tri; Bachtiar, Jasmine Chanifah U (RUAS, 2021)
The existence of landmarks on campus can help students to access campus facilities in supporting formal teaching and learning activities. However, homogeneous planning of landmarks can divert student orientation in accessibility, particularly for freshman. This was partly complained by students such as students of the Institut Teknologi Bandung (ITB), Indonesia. Therefore, it is prominent to identify the process of recognizing landmarks as well as their attributes and meanings that can strengthen the process of forming cognitive maps. The current study aims to determine the cognitive map differences of freshmen freshmen in ITB who have had prior spatial experience (architecture students) (N=18) and students who have not before (N=20). This qualitative research was conducted by distributing questionnaires to compare student cognitive maps. The results showed that architecture students identify fewer landmarks than non-architecture students. However, architecture students have an appropriate cognitive map, so they are likely not to get lost on campus. Meanwhile, the attributes of the landmarks identified are additional accessories; shape; detail/ornamentation; design style; height; composition; location; material/texture; proportion; singularity; scale; and colour. The meanings of landmarks identified are history, memory, structure, sensation, and emotional feeling. This result is expected to be used as references for designing other ITB campus landmarks.